2014
DOI: 10.1007/s00586-014-3413-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neck movement smoothness between patients with mechanical neck disorder and healthy volunteers using the spectral entropy method

Abstract: The spectral entropy would be suitable to discriminate the smoothness of cervical movement between patients with MND with healthy volunteers and demonstrated patients with MND had significantly less smooth cervical movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Distinct modulations of motor unit synchronization among patients with MND and asymptomatic individuals observed in the present investigation subscribe to the assertion that patients with MND used altered neuromuscular control strategies to achieve the prescribed task compared to asymptomatic subjects. Since the plastic modulation of motor unit synchronization is generally thought to originate from common synaptic input branched presynaptic neurons [31, 32], it is most likely that the reduction in motor unit synchronization reflects the poor cortico-motoneuronal connections, which would be consistent with decreases in muscular strength and presences of jerky or irregular movements for patients with neck pain [2, 9, 10]. Furthermore, another interesting issue should be further elaborated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct modulations of motor unit synchronization among patients with MND and asymptomatic individuals observed in the present investigation subscribe to the assertion that patients with MND used altered neuromuscular control strategies to achieve the prescribed task compared to asymptomatic subjects. Since the plastic modulation of motor unit synchronization is generally thought to originate from common synaptic input branched presynaptic neurons [31, 32], it is most likely that the reduction in motor unit synchronization reflects the poor cortico-motoneuronal connections, which would be consistent with decreases in muscular strength and presences of jerky or irregular movements for patients with neck pain [2, 9, 10]. Furthermore, another interesting issue should be further elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…MND is defined as generalized neck pain and disability without any abnormal anatomical structures or identifiable orthopedic and neurological problems, such as spinal vertebral fracture, exceptional spinal lordosis, spinal spondylosis, spinal osteoarthritis and so on [1]. Clinically, the symptoms of neck pain, abnormal cervical kinematics, neck muscle weakness and neck-related functional disabilities are the common complaints for patients with MND [110]. Although the etiology of MND is largely under debate, it is believed that prolonged workloads and poor work postures are potential underlying causes [11–13].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency characteristics were analyzed by calculating the power spectral density after Fourier transformation for the velocity data of vertical hand movement (cf. Yang et al, 2014 ). From the calculated spectrum density, we divided the whole frequency components into fundamental frequency components and 2, 3, and 4 times frequency components.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, a classification framework combining information spectrum entropy [18,19] with SVM method [20,21] is proposed to extract effective feature vectors of infrasound signals generated by earthquakes, tsunamis and volcanic events, followed by infrasound signal classification. The integrated classification framework proposed in this study is also shown in Fig.…”
Section: Methodsmentioning
confidence: 99%